2011
DOI: 10.1038/nature09909
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Senescence and tumour clearance is triggered by p53 restoration in murine liver carcinomas

Abstract: Although cancer arises from a combination of mutations in oncogenes and tumour suppressor genes, the extent to which tumour suppressor gene loss is required for maintaining established tumours is poorly understood. p53 is an important tumour suppressor that acts to restrict proliferation in response to DNA damage or deregulation of mitogenic oncogenes, by leading to the induction of various cell cycle checkpoints, apoptosis or cellular senescence 1,2 . Consequently, p53 mutations increase cell proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In response to DNA damage, proliferating cells can either repair the damage and resume growth, or activate anti-proliferative programs such as cell death (apoptosis) or senescence, a state characterized by the long-term enforcement of cell cycle arrest and the loss of recovery potential (Fig 1A). While pro- apoptosis therapy has been used for several decades as a tool for destroying the growth of cancerous cells, recent studies also highlighted the therapeutic potential of pro-senescence cancer therapy (Collado and Serrano, 2010; Nardella et al, 2011; Xue et al, 2011). However, as opposed to apoptosis, which is a terminal cell fate, senescing cells require continuous activation of the pathways responsible for maintaining the arrested state (Beauséjour et al, 2003; Dirac and Bernards, 2003) (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…In response to DNA damage, proliferating cells can either repair the damage and resume growth, or activate anti-proliferative programs such as cell death (apoptosis) or senescence, a state characterized by the long-term enforcement of cell cycle arrest and the loss of recovery potential (Fig 1A). While pro- apoptosis therapy has been used for several decades as a tool for destroying the growth of cancerous cells, recent studies also highlighted the therapeutic potential of pro-senescence cancer therapy (Collado and Serrano, 2010; Nardella et al, 2011; Xue et al, 2011). However, as opposed to apoptosis, which is a terminal cell fate, senescing cells require continuous activation of the pathways responsible for maintaining the arrested state (Beauséjour et al, 2003; Dirac and Bernards, 2003) (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in recent years, several regulators of PICS have been identified. For instance, the inhibition of S-phase kinase-associated protein 2 (Skp2) restores senescence in PTEN-and p53-deficent tumors through the upregulation of p27 (351). SMAD4 inactivation or overexpression of COUP-TFII, a SMAD4 inhibitor, also promotes the bypass of PICS by allowing the transcription of cyclin D1 in Ptennull tumors (263).…”
Section: Oncogene-induced Senescencementioning
confidence: 99%
“…Since it is likely that even a small percentage of senescent cells can promote substantial deleterious effects, there may be natural mechanisms that clear these senescent cells in vivo to maintain overall fitness. One primary response to p53 activation in murine liver carcinoma was found to be the accumulation of senescent cells, which were subsequently shown to be cleared by the innate immune response (Xue et al, 2011). NK cells were also found to eliminate senescent cells in vivo by perforin (Prf) mediated granule exocytosis (Sagiv et al, 2013) and Prf1 −/− mice showed a 4X accumulation of senescent cells and a 21% decrease in median lifespan, which was alleviated by senescent cell clearance (Ovadya et al, 2018).…”
Section: Cellular Senescence and Organismal Agingmentioning
confidence: 99%